La radiologia medica Official Journal of the Italian Society of Medical Radiology - Giovagnoni, Andrea; SpringerLink (Online service) (Milan : Springer Milan : Imprint: Springer.)
La radiologia medica, founded by Felice Perussia in 1914, is a peer-reviewed journal and the official organ of the Italian Society of Medical Radiology (SIRM). The journal is intended as a medium for the communication of results and developments in the field of Radiology, particularly on advances in diagnostic imaging and its allied sciences. The journal welcomes original contributions on both basic and clinical aspects of modern radiology and therapy, including diagnostic radiology and interventional techniques, with special emphasis on modern imaging techniques, radiotherapy, nuclear medicine, radiobiology and health physics. A distinguished Editorial Board and a selection of reports published in the form of original articles, review articles, editorials, short communications and letters to the editor render this publication indispensable for radiologists and related specialists. As of 2014 the journal is published monthly, online only and in English language. The Journal aims at being a forum for the international radiological community, therefore contributions coming from authors working in countries other than Italy are welcome. The journal visibility in the scientific community is further enhanced by its online edition, available at www.springerlink.com.
Keywords: Radiology; Interventional radiology; Neuroradiology; Imaging / Radiology; Diagnostic Radiology; Interventional Radiology; Neuroradiology; Ultrasound